USM STUDENT, ALUMNI REPRESENT MALAYSIA AT PHILIPPINES REGIONAL MEET - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 5 April 2017 Siti Zurianah Ismail, a Universiti Sains Malaysia (USM) graduate student in Islamic Finance and Ameera Nadia Shafiee, a 2013 USM alumna have been selected to represent the Society for the Development of Human Resources for Rural Areas (DHRRA) Malaysia at the DHRRA ASEAN conference in the regional Training of Trainers (TOT) Module 2 programme in Cebu, Philippines recently.